2021
DOI: 10.3389/fpsyg.2021.750127
|View full text |Cite
|
Sign up to set email alerts
|

Increased Working From Home in Vocational Counseling Psychologists During COVID-19: Associated Change in Productivity and Job Satisfaction

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, vocational counselors in Switzerland more frequently worked from home (WFH) and less frequently worked on-site. The aim of this study was to assess how WFH corresponds with indicators of job performance and occupational wellbeing. More specifically, the current questionnaire study analyzed the increase in WFH, self-reported productivity, distractibility in WFH, current job satisfaction, work-life balance in WFH, and feeling of loneliness. Findings showed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
(75 reference statements)
1
13
0
2
Order By: Relevance
“…Recent research during the COVID-19 outbreak has shown that job crafting can be useful in dealing with the negative effects of work overload, especially when working from home [130]. Finally, since the worktime boundary between work and private life could gradually disappear when working from home [131], interventions should be aimed at helping workers to preserve a clear physical or psychological distinction (i.e., segmentation) between work and non-work domains (e.g., walking around the block as an alternative commuting strategy when working from home) [132].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Recent research during the COVID-19 outbreak has shown that job crafting can be useful in dealing with the negative effects of work overload, especially when working from home [130]. Finally, since the worktime boundary between work and private life could gradually disappear when working from home [131], interventions should be aimed at helping workers to preserve a clear physical or psychological distinction (i.e., segmentation) between work and non-work domains (e.g., walking around the block as an alternative commuting strategy when working from home) [132].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Although many studies have investigated the impact of WFH on work productivity during COVID-19, the results varied by population, setting, occupation, and time of measurement 8–18 . Only a few studies have measured the impact of WFH on absenteeism and presenteeism due to health problems during the pandemic 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased work productivity was also observed among a working population in Austria, 14 workers in manufacturing firms in Japan, 12 and a representative sample of employees and employers in Japan 18 . On the other hand, increased work productivity was observed among certain professions who worked from home only part time in the United States, 11 vocational counseling psychologists in Switzerland, 13 inpatient and infusion pharmacists at a US comprehensive cancer center, 15 pediatric neuroradiologists in a US quaternary pediatric academic hospital, 16 and public health workers from a large local health district in Australia 17 …”
mentioning
confidence: 95%
See 2 more Smart Citations